“The Cliché to end all Clichés” – Test Tube Tooth - Arya, Geeta (Journal of Medicine and Health Sciences Research, 2019)
For quite a while now, experts in the field of tissue building have been endeavouring to bioengineer dental tissues and furthermore whole teeth. With the true objective to achieve a whole tooth through dental planning, that has the identical or about same natural, mechanical and physical properties of a trademark tooth, it’s imperative to deal with all of the cells and tissues which are stressed over the course of action, upkeep, and fix of the tooth. In this article, we review the methods related with odontogenesis or organogenesis of a tooth and headway in the bioengineering of a whole tooth.